Burnout among nurses working in the primary health care centers in Saudi Arabia, a multicenter study - Mohammed Adeeb Shahin; Sami Abdo Radman Al-Dubai; Duoaa Seddiq Abdoh; Abdullah Saud Alahmadi; Ahmed Khalid Ali; Tamer Hifnawy (AIMS Press, 2020)
Background: Burnout is a common psychosocial phenomenon among nursing. It has been attributed to prolonged exposure to stress in the work place. This study aimed to determine the prevalence and associated factors of burnout among nurses in the primary health care centers in Saudi Arabia. Methods: This cross-sectional study was conducted among 200 nurses by using a self-administered questionnaire. Maslach Burnout Inventory-Human Services Survey (MBI-HSS) was used to measure burnout. Results: Most participants were females (73.0%) and aged ≤35 years (52.0%). About 39% had high emotional exhaustion, 38% had high depersonalization and 85.5% had low personal accomplishment. About 89% (178) scored high at least on one subscale of burnout. Burnout was associated with age, educational level and sources of stress in the workplace. Conclusion: Level of burnout among nurses was high and was associated mainly with stressors in the workplace. Improving work environment and management of stress in the workplace should be a priority to minimize burnout among nurses.